Program Tahfizd Qur’an untuk Menghasilkan Peserta Didik Penghafal Al-Qur’an Yang Berkarakter Serta Menguasai Ilmu Pengetahuan dan Pandai Membaca Al-Qura’an Dengan Benar di SMPN 3 Kinali - Fauziah, Fauziah; Wati, Salmi; Siskaramayanti, Siskaramayanti (Indonesian Research Journal on Education, 2023)
This research is motivated by a Tahfidz al-Qur'an program that has been carried out by a schooleducation at SMPN 3 Kinali, which is based on that reading the Koran is something that is mandatoryand must be done by every Muslim. without exception. However, there are still some students who are not fluent in reading the Koran correctly, so these students will be fostered in the process of reading the Koran correctly so that they can memorize the Koran easily through the iqra' program. And also with the tahfidz al-Qur'an program, students are not only good at reading but also have to practice what is in the contents of the al-Qur'an. Indeed, in reading the Koran in Arabic, we must also learn the meaning andunderstand the meaning of the verses of the Koran. So the research focused on a program implemented at SMPN 3 Kinali, namely the tahfidz Qur'an program, which is an excellent program that is carried out to produce students who memorize the Koran and shape the character of students, master science and be able to read al-Quran. -Quran properly. With the tahfidz Qur'an program, students will be coached on how to read the Koran correctly and how morals must be applied as memorizers of the Koran.